2014
DOI: 10.1103/physrevlett.113.182502
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Quantum Shells and Orientation in Quasifission

Abstract: The quasi-fission mechanism hinders fusion in heavy systems through breakup within zeptoseconds into two fragments with partial mass equilibration. Its dependence on the structure of both the collision partners and the final fragments is a key question. Our original approach is to combine an experimental measurement of the fragments' mass-angle correlations in 40 Ca+ 238 U with microscopic quantum calculations. We demonstrate an unexpected interplay between the orientation of the prolate deformed 238 U with qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
209
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(224 citation statements)
references
References 63 publications
(134 reference statements)
15
209
0
Order By: Relevance
“…Although this approach has been widely used, it could have limitations due to the fact that quasifission is not a statistical decay but a dynamical process, and that fusion-fission could be asymmetric due to, e.g., late-chance fusion-fission at low excitation energies [28] as well as shell structure of pre-scission configurations [29]. Correlations between mass and scattering angle of the fragments have also been measured extensively [25,[30][31][32][33]. In particular, they can be used to disentangle fast quasi-fission processes (few zeptoseconds) to longer reaction mechanisms associated with contact times between the fragments exceeding 10 − 20 zs (i.e., long-time quasifission and fusion-fission).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although this approach has been widely used, it could have limitations due to the fact that quasifission is not a statistical decay but a dynamical process, and that fusion-fission could be asymmetric due to, e.g., late-chance fusion-fission at low excitation energies [28] as well as shell structure of pre-scission configurations [29]. Correlations between mass and scattering angle of the fragments have also been measured extensively [25,[30][31][32][33]. In particular, they can be used to disentangle fast quasi-fission processes (few zeptoseconds) to longer reaction mechanisms associated with contact times between the fragments exceeding 10 − 20 zs (i.e., long-time quasifission and fusion-fission).…”
Section: Introductionmentioning
confidence: 99%
“…The Hartree-Fock approximation and its time-dependent generalization, the time-dependent Hartree-Fock theory, have provided a possible means to study the diverse phenomena observed in low energy nuclear physics [41,42]. In general modern TDHF calculations provide a useful foundation for a fully microscopic many-body description of large amplitude collective motion including collective surface vibrations and giant resonances [48][49][50][51][52][53][54][55][56][57][58][59][60][61] nuclear reactions in the vicinity of the Coulomb barrier, such as fusion [36,39,[62][63][64][65][66][67][68][69], deepinelastic reactions and transfer [70][71][72][73][74][75][76], and dynamics of (quasi)fission fragments [33,[43][44][45][46][47].…”
Section: Formalism a Tdhf And Dc-tdhf Approachesmentioning
confidence: 99%
See 3 more Smart Citations